"Everything has changed": detention officer roles and recreation time changes due to COVID-19 policies at a Southwest County Jail - Travis Pinn; Heather Williamson; Bethany Robinson; Sara Shuman; Maria Evans; George Pro; Ricky Camplain (BMC, 2022)
Abstract Background The COVID-19 pandemic responses in jails have forced detention officers to adjust how they approach the confinement and care of individuals while they are incarcerated. One aspect of incarceration affected was detention officers' roles. The aims of this research project were to determine how the COVID-19 pandemic has affected the general duties of detention officers at a Southwest County Jail. Detention officers were recruited via email to participate in an online questionnaire from October to December 2020. Participants answered Likert scale and open-ended questions regarding how the COVID-19 pandemic has affected their job duties. Descriptive statistics and thematic analysis were used to identify themes and patterns in the responses. Results Among 24 detention officers, 87% indicated agreement that the COVID-19 pandemic has significantly changed the duties of detention officers at CCDF. The most discussed change was the introduction of a 14-day quarantine process for newly incarcerated individuals. The 14-day quarantine increased the workload of detention officers. Conclusion The COVID-19 pandemic responses in jail may have unintended negative consequences for the job duties of detention officers. Current and future pandemic response strategies in jails would benefit from taking staff perspectives into consideration as they are directly impacted by the COVID-19 response strategies put into place. Policy implications are discussed.